Errears and erroriboose : Joyce and error - Creasy, Matthew, 1974- (European Joyce studies ;, 2011)
Joyce was fascinated by error throughout his writing career, from the malapropisms of characters in Dubliners, through to misquotations and misappropriations in A Portrait of the Artist as a Young Man and the errors and gaffes committed by Leopold Bloom in Ulysses . This interest culminates in the ceaseless perversions of language, perspective and fact in Finnegans Wake . Error is not, however, something that Joyce only writes about: it happens to him and his texts in the form of misprints and inadvertent factual errors, through the interventions of others and through lapses in Joyce's own pr.